Polymer-Oxygen Scavenger for Oil Recovery in Sandstone - Jati, Dhika Permana; Hetharia, Putri Diantha; Damayandri, Dadan; Widyaningsih, Ratna; Kaesti, Edgie Yuda; Taufantri, Yudha; Putra, Ilham Ardatul (Testing Center for Oil and Gas LEMIGAS, 2026)
Polymer degradation caused by dissolved oxygen remains a major challenge in Enhanced Oil Recovery (EOR) for sandstone reservoirs, especially under moderate salinity (18,000 ppm) and temperature (60°C) conditions, which accelerate viscosity loss. While HPAM polymers are highly effective, ensuring their long-term stability requires strategies that preserve molecular integrity throughout the injection process. This study employs laboratory experiments to assess two HPAM variants (FP 3630 and FP 3230), both in conventional formulations and with an oxygen scavenger (NaHSO₃), using Bentheimer synthetic cores. Evaluations cover fluid-to-fluid (compatibility, rheology, filtration, thermal stability) and fluid-to-rock (injectivity, core flooding) performance under reservoir conditions. Results identify FP 3630 at 1400 ppm with 0.1% NaHSO₃ as the optimal formulation. The oxygen scavenger significantly improves thermal stability and reduces viscosity degradation from 32.83% to 4.24%. This formulation achieves an ideal Resistance Factor (11.44) and causes minimal formation damage (RRF 1.01), while enhancing the Recovery Factor from 67.38% to 87.29%. These findings confirm that the incorporation of oxygen scavengers effectively minimizes polymer degradation and establishes them as a crucial component for the successful implementation of EOR in moderate-salinity sandstone reservoirs.